Oxidative stress caused by the use of preemergent herbicides in rice crops - Langaro, Ana; Agostinetto, Dirceu; Ruchel, Queli; Garcia, Jessica; Perboni, Lais (Revista Ciência Agronômica, 2016)
Among the methods of weed control, stands out chemical control. However, even selective, herbicides can trigger the production of reactive species of oxygen and cause oxidative stress. The aim of the study was to evaluate changes in photosynthetic parameters, oxidative damage, antioxidant enzyme activity and altered metabolism of rice plants after applying pre-emergent herbicides. The experiment was conducted in a greenhouse and herbicides used were oxadiazon, pendimethalin and oxyfluorfen, beyond the control without herbicide. There was a reduction of photosynthetic rate and efficiency of carboxylation, compared to the control, when applied herbicides oxyfluorfen and pendimethalin. The major lipid peroxidation and proline accumulation was observed for the herbicide oxyfluorfen. The oxyfluorfen and oxadiazon herbicides also resulted in increased activity of superoxide dismutase, compared to control. When evaluated ascorbate peroxidase activity, there was a higher enzyme activity in plants treated with oxadiazon and pendimethalin. Even selective herbicides registered for weed control in rice crops cause phytotoxicity, reduce height and alter the metabolism of plants, generating reactive oxygen species, which activate enzymatic and non-enzymatic defense systems and result in the degradation of photosynthetic pigments and in reduced protein content.